2021
DOI: 10.3390/foods10030584
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Transfer Study: Transfer of Bromoform Present in Asparagopsis taxiformis to Milk and Urine of Lactating Dairy Cows

Abstract: Enteric methane (CH4) is the main source of greenhouse gas emissions from ruminants. The red seaweeds Asparagopsis taxiformis (AT) and Asparagopsis armata contain halogenated compounds, including bromoform (CHBr3), which may strongly decrease enteric CH4 emissions. Bromoform is known to have several toxicological effects in rats and mice and is quickly excreted by the animals. This study investigated the transfer of CHBr3 present in AT to milk, urine, feces, and animal tissue when incorporated in the diet of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 25 publications
2
46
0
1
Order By: Relevance
“…The anti-methanogenic effect was attributed to halogenated compounds such as bromoform, dibromochloromethane and dibromethane [ 10 , 13 ]. The toxicity and ozone degrading properties of halocarbons are well known, and there are both health and environmental concerns related to the use of Asparagopsis taxiformis as a feed additive [ 14 ]. Brown seaweeds have also shown anti-methanogenic potential [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-methanogenic effect was attributed to halogenated compounds such as bromoform, dibromochloromethane and dibromethane [ 10 , 13 ]. The toxicity and ozone degrading properties of halocarbons are well known, and there are both health and environmental concerns related to the use of Asparagopsis taxiformis as a feed additive [ 14 ]. Brown seaweeds have also shown anti-methanogenic potential [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palatability aspects might contribute to explain the interaction, as low palatability has been reported in some studies with Asparagopsis spp. (Muizelaar et al, 2021;Stefenoni et al, 2021), and in contrast, no palatability issues were found with 3-NOP (Lee et al, 2020).…”
Section: )] or 3-nitrooxypropanol (3-hydroxypropyl Nitrate Or 3-nop)mentioning
confidence: 74%
“…The role of bromoform and bromochloromethane as active ingredients in Asparagopsis raises challenges from a regulatory and market acceptability perspective, given that both substances are confirmed animal carcinogens and probable/possible human carcinogens. Animal trials have detected residues in urine and milk [90], but no detrimental effects on meat quality [91]. There are also open questions regarding palatability to livestock, animal health and the ability to produce and supply seaweed at a large scale, especially to extensively grazed livestock [88][89][90]92].…”
Section: (D) Methane Inhibitors: Seaweedmentioning
confidence: 99%
“…Animal trials have detected residues in urine and milk [90], but no detrimental effects on meat quality [91]. There are also open questions regarding palatability to livestock, animal health and the ability to produce and supply seaweed at a large scale, especially to extensively grazed livestock [88][89][90]92].…”
Section: (D) Methane Inhibitors: Seaweedmentioning
confidence: 99%